Belief-Dependent Motivations and Psychological Game Theory - Pierpaolo Battigalli; Martin Dufwenberg (Center for Economic Studies and ifo Institute (CESifo), 2020)
The mathematical framework of psychological game theory is useful for describing many forms of motivation where preferences depend directly on own or others' beliefs. It allows for incorporating, e.g., emotions, reciprocity, image concerns, and self-esteem in economic analysis. We explain how and why, discussing basic theory, experiments, applied work, and methodology.
Keywords: C72; D91; 330; psychological game theory; belief-dependent motivation; reciprocity; emotions; image concerns; self-esteem